Parallel-ridge pattern on dermatoscopy: observation in a case of purpura traumatica pedis - Feci, Luca (Dermatol Pract Concept, 2015)
Dermatologists are often referred urgent cases of acral hematoma by general practitioners and sports medicine specialists for the purpose of excluding warts, nevi or melanoma. Acral hematoma is often a cause of anxiety to patients and their families. Here, we report a case of purpura traumatica pedis, referred to us as suspected plantar melanoma because of the finding of parallel-ridge pattern on dermatoscopic examination. To avoid unnecessary and costly procedures, doctors should inquire about any episode of physical exertion before the onset of purpura, recording the lesion’s anatomic site (e.g., unilateral vs. bilateral involvement) and clinical features.